Pré-condicionamento das sementes de mamoneira para o teste de tetrazólio - Gaspar-Oliveira, Carolina Maria [UNESP]; Martins, Cibele Chalita [UNESP]; Nakagawa, Joao [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2011)
Preconditioning of castor bean seeds for the tetrazolium test. This research had the objective of standardizing the methodology for preconditioning of castor bean (Ricinus communis L.) seeds for the evaluation of their physiological potential by the tetrazolium test. The evaluated seed preconditioning methods were: seeds with coat between moist paper towel at 30, 35 and 40 degrees C for 6, 8, 10, 12, 14, 16 and 18 hours; and seeds without coat between moist paper towel; and seeds with coat immersed in water, at 25, 30, 35 and 40 degrees C for 1, 2, 3, 4, 5 and 6 hours. After preconditioning, the seed coat was removed, the seeds were cut lengthwise, and immersed in tetrazolium solution at a concentration of 0.2% for 120 minutes at 35 degrees C. The seeds' germination percentage, moisture content before and after preconditioning, and staining uniformity after the tetrazolium were evaluated. The statistical design was completely randomized, and the means comparisons were accomplished by the Tukey test at 0.05 level of probability. It was concluded that castor bean seeds should be preconditioned with coat between moist paper towel at 35 degrees C for 12 hours, so that the results of the tetrazolium test will be similar to those obtained in the germination test.
Preconditioning of castor bean seeds for the tetrazolium test
Keywords: viability; castor bean; methodology; physiological potential